Toward a New Model of Scientific Publishing: Discussion and a Proposal - Kravitz, Dwight; Baker, Chris I. (Frontiers in Computational Neuroscience, 2011)
The current system of publishing in the neurosciences, is notable for its redundancy, inconsistency, sluggishness, and opacity. These problems persist, and grow worse, because of a continuing failure to fully leverage new technology. Online access has eliminated space limits within peer-reviewed journals, yet we continue to deny publication. Each submission of a rejected manuscript requires the entire machinery of peer review to creak to life. This redundancy causes delays, inconsistency, and increases the burden on authors, reviewers, and editors. Further, reviewers serve a key role in the process but their performance is not tracked; yet alone rewarded. This misalignment of incentives contributes to the inconsistency and sluggishness that pervades peer review. The current system also interferes with the primary purpose of modern journals, providing a quick way of prioritizing the literature. Reviews are written to gauge publication rather than scientific merit and there is no guarantee that the journal’s criteria agree with those of an individual researcher, making any prioritization opaque and noisy at best. The focus of this special issue is the future form of post-publication reception, and the development of a marketplace where a paper rises and falls based on its reception from the field. However, the information that accompanies a paper into the marketplace is as important as the marketplace’s mechanics. Beyond suggestions as to the mechanisms of reception, we propose an update to the system of publishing in which publication is guaranteed, but pre-publication peer review still occurs, giving the authors the opportunity to revise their work following a mini pre-reception from the field. This step also provides a consistent set of rankings and reviews to the marketplace, allowing for early prioritization and stabilizing its early dynamics. We further propose to improve the general quality of reviewing by providing tangible rewards to those who do it well.